Relasi Akal dan Wahyu Era Modern (Analisis Teologis Pemikiran Ibnu Taymiyyah) - Sindi Lestari; Ismail Ismail (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2024)
Abstract: The results of this study are; 1) Ibn Taymiyyah adheres to tauhid uluhiyah because rububiyyah has included it. Ibn Taimiyah divided the concept of Tauhid into three parts, Tauhid Asma' Wa-asshifat, Tauhid Uluhiyyah and Tauhid Rububiyah. Ibn Taimiyyah prioritized revelation over reason, revelation was considered higher than reason but did not leave reason behind, he equated reason and revelation by viewing the position of reason as "gharizah". Ibn Taimiyah's thoughts on the relationship between reason and revelation, namely by concluding that revelation is higher than philosophy and then also trying to reconcile reason and revelation by relating reason and revelation in interpretation in order to understand the sharia by returning to the concept of its suitability because it involves reason. according to him reason and revelation are in harmony. Real revelation and a straight intellectual perspective are always in line. Ibn Taymiyyah formulated the concept of conformity to overcome the conflict between reason and revelation. 2) Theological analysis of Mrs. Taymiyyah's thoughts on the relationship between reason and revelation that has an impact on the modern era with its advantages and disadvantages, namely there are 5 components, first, revelation is prioritized over reason, second, reason may be equal to revelation, third, the conflict between reason and revelation by prioritizing reason, fourth, Ibn Taymiyyah's method of interpretation and fifth, Ibn Taymiyyah's concept of fitrah. Ibn Taymiyyah's thoughts contributed to the progress of the modern era in several fields, first, Ibn Taymiyyah is used in a number of modern disciplines, second, Ibn Taymiyyah's modern Tafsir Al-Quran, third, Islamic Law is influenced by Ibn Taymiyyah, fourth, The impact of modern politics from Ibn Taymiyyah, fifth, Ibn Taymiyyah's Contribution to the modern economy, sixth, Ibn Taymiyyah's Influence on modern thought. Keywords: The Relationship between Reason and Revelation in the Modern Era. Abstrak: Hasil penelitian ini adalah; 1) Ibnu Taymiyyah menganut tauhid uluhiyah. Ibnu Taimiyah membagi pengertian Tauhid menjadi tiga bagian, Tauhid Asma' Wa-asshifat, Tauhid Uluhiyyah dan Tauhid Rububiyah. Ibnu Taimiyyah memprioritaskan wahyu dari pada akal, wahyu dianggap lebih tinggi dari akal namun tidak menerbelakangi akal, beliau menyama ratakan akal dan wahyu dengan memandang posisi akal sebagai “gharizah”. Pemikiran Ibnu Taimiyah pada relasi akal dan wahyu yaitu dengan model menyimpulkan bahwa wahyu lebih tinggi dari filsafat kemudian juga berupaya mendamaikan akal dan wahyu dengan merelasikan akal dan wahyu dalam takwil guna memahami syariat dengan kembali pada konsep kesuaiannya karena melibatkan akal menurutnya akal dan wahyu adalah selaras. Ibnu Taimiyah merumuskan konsep kesesuaian guna mengatasi konflik antara akal dan wahyu.2) Analisis teologis pemikiran Ibu Taymiyyah terhadap relasi akal dan wahyu yang berdampak pada era modern dengan kelebihan dan kekurangannya yaitu ada 5 komponen, pertama, wahyu lebih diprioritaskan dari pada akal, kedua, akal boleh setara dengan wahyu, ketiga, konflik relasi akal dan wahyu dengan mendahulukan akal, keempat, metode penafsiran Ibnu Taymiyyah dan yang kelima, konsep fitrah Ibnu Taymiyyah. Pemikiran Ibnu Taimiyah berkontribusi dalam kemajuan era modern dalam beberapa bidang, pertama, Ibnu Taimiyah digunakan dalam sejumlah disiplin ilmu modern, kedua, Tafsir Al-Quran modern Ibnu Taimiyyah, ketiga, Hukum Islam dipengaruhi oleh Ibnu Taimiyah, keempat, Dampak politik modern dari Ibnu Taimiyah, kelima, Kontribusi Ibnu Taimiyah terhadap perekonomian modern, keenam, Pengaruh Ibnu Taimiyyah terhadap pemikiran modern. Kata kunci : Relasi Akal dan Wahyu Era Modern.